Modification of the morphology, porosity and surface chemistry of lignin-based electrospun carbon materials - Ruiz-Rosas, Ramiro Rafael; Rodríguez-Mirasol, José; Rosas-Martínez, Juana María; García-Mateos, Francisco José; Cordero-Alcántara, Tomás (My University, 2019)
Lignin is a biopolymer that can be found as the main component of plants. It is obtained as a coproduct in the papermaking and biofuel industries. Owing to its high carbon and aromatic content, high availability and reduced cost, it is an excellent precursor for the preparation of highly valued carbon materials. Electrospinning is a suitable top-down technique for the preparation of polymeric fibers using high voltage electrical fields and polymer solutions of proper viscosity and conductivity. Organosolv lignins, which are extracted from lignocellulosic biomass using organic solvents, are soluble in ethanol, obtaining a solution that matches the requirement of the electrospinning process. In this way, it is possible to produce lignin-based porous carbon fibers using a coaxial electrospinning device [1]. This contribution summarizes our findings about the preparation of carbon materials with different morphologies and composition by processing lignin using electrohydrodynamic forces. Lignin spheres, beaded fibers, straight fibers, beaded tubes and straight tubes are obtained by using coaxial and triaxial spinnerets that allows the electrospinning of two or three different solutions at once [1], Fig. 1. Thermal stabilization in air is needed in order to avoid melting of lignin fibers during carbonization. Stabilization times of 48-96 hours are usually required in this step, decreasing the sustainability of the production process. Phosphoric acid can be added in small amounts in the lignin solution, shortening the time for achieve a successful thermostabilization of the fiber [2]. The carbonized materials show narrow microporosity and large surface area values (SBET from 600 to 1000 m2g-1) and additional pore size and volume can be developed by controlled gasification.
Keywords: Carbón activado; Fibras; Lignina; Electrospinning; Materiales de carbono